2011
DOI: 10.1007/s00467-010-1724-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure profile in renal transplant recipients and its relation to diastolic function: tissue Doppler echocardiographic study

Abstract: Hypertension is a common complication after renal transplantation and is associated with increased risk of cardiovascular disease. The aim of the current study was to investigate the diurnal blood pressure pattern and its relation to structural and functional cardiac changes in renal transplant recipients. Sixty-six stable renal transplant patients (34 female, 32 male), aged 7 to 25 years (mean 17.4±4.3 years) were enrolled in this study. Cardiac function assessed by tissue Doppler echocardiography and blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 25 publications
4
32
2
Order By: Relevance
“…This is similar to or slightly higher that the prevalence of 19-31%, reported in previous studies 14,16,18-20,30 although most of these studies reported a higher prevalence of sustained hypertension. Importantly, even patients taking antihypertensive medications frequently were found to have masked and sustained hypertension, suggesting that hypertension is both underdiagnosed and inadequately treated in this population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is similar to or slightly higher that the prevalence of 19-31%, reported in previous studies 14,16,18-20,30 although most of these studies reported a higher prevalence of sustained hypertension. Importantly, even patients taking antihypertensive medications frequently were found to have masked and sustained hypertension, suggesting that hypertension is both underdiagnosed and inadequately treated in this population.…”
Section: Discussionsupporting
confidence: 87%
“…Some have found an association of abnormal ABP status with LVMI, 4,13,20,29,34 , with others did not confirm this finding 17,35,36 . Given a large size of study population we were able to stratify patients according to both ABP results and BP treatment and to clarify previous data of a higher prevalence of LVH in patients with controlled hypertension (treated) compared with normotensive patients not receiving BP medications.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, ABPM showed that 75.7% of their patients were hypertensive. 28 We recorded hypertension in 43.4% and 86% of patients measured by the conventional method and ABPM. The significant difference between the prevalence of hypertension defined by our 2 methods warrant the risk of missed hypertension and consequently, LVH in kidney transplanted recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Long-standing hypertension has been shown to result in LVH and increased LVMI and cIMT, all known risk factors for CVD (2). LVH is prevalent in approximately 50% of patients with CKD and ESRD and in kidney transplant recipients.…”
Section: Effect Of Hypertension On Cvd and Allograft Functionmentioning
confidence: 99%